Ultrastructural features mirror metabolic derangement in human endothelial cells exposed to high glucose - Roberta Scrimieri; Laura Locatelli; Alessandra Cazzaniga; Roberta Cazzola; Emil Malucelli; Andrea Sorrentino; Stefano Iotti; Jeanette A. Maier (Scientific Reports, 2023)
Abstract High glucose-induced endothelial dysfunction is the early event that initiates diabetes-induced vascular disease. Here we employed Cryo Soft X-ray Tomography to obtain three-dimensional maps of high d-glucose-treated endothelial cells and their controls at nanometric spatial resolution. We then correlated ultrastructural differences with metabolic rewiring. While the total mitochondrial mass does not change, high d-glucose promotes mitochondrial fragmentation, as confirmed by the modulation of fission–fusion markers, and dysfunction, as demonstrated by the drop of membrane potential, the decreased oxygen consumption and the increased production of reactive oxygen species. The 3D ultrastructural analysis also indicates the accumulation of lipid droplets in cells cultured in high d-glucose. Indeed, because of the decrease of fatty acid β-oxidation induced by high d-glucose concentration, triglycerides are esterified into fatty acids and then stored into lipid droplets. We propose that the increase of lipid droplets represents an adaptive mechanism to cope with the overload of glucose and associated oxidative stress and metabolic dysregulation.